RURAL AND SUSTAINABLE DEVELOPMENT: CONTRIBUTION FROM SOCIAL WORK TO THE LIVESTOCK SECTOR IN THE MUNICIPALITIES OF CIRCASIA AND FILANDIA OF THE DEPARTMENT OF QUINDÍO, COLOMBIA - Carol Daniela Jimenez Avila (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
Social Work contributes significantly to making visible the need for the livestock sector to assume processes of associativity and integrate the family in the different links of the productive chain as a point of social balance. This manuscript addresses the importance of promoting associativity and competitiveness scenarios, considering the need to implement agricultural technological tools that generate added value to dairy production and favor participation in local, national and international economies. The research involved: the Approach and characterization of the producers of two associations, the Association of Milk Producers of Circasia (hereinafter APROLACIR); Association of Agricultural Producers of Filandia (hereinafter ASOPROAGRO); Design of the technological application. In this sense, the R + D + I process (Research + Development + Technological Innovation) made it possible to consolidate direct participation with the population and the activities involved in the production chain.